The Extinction of Local Languages in Indonesia and Strategies to Overcome (Comparative Study in West Kalimantan and North Maluku) - Abdul Muin (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
The extinction of local languages in West Kalimantan and North Maluku is a growing concern. This study address the following questions: 1) How diverse are the local languages in West Kalimantan and North Maluku? 2) What is the current condition of these local languages? 3) How can the extinction of these languages be prevented? This research utilizes a comparative study method with a descriptive qualitative approach, focusing on the status of local languages in these regions. Data was collection through literature review, observation, interviews, and documentation. The findings indicate that many local languages in these areas are on the brink of extinction, primarily due to the diminishing number of speakers. Additionally, the dominance of the national language, Indonesian, has pushed local languages aside, especially among the younger generation who prefer using Indonesian in daily interactions. Despite this, the use of local languages remains strong within families and communities If immediate action is not taken, these languages ​​will likely become extinct in the coming decades. This research emphasizes the need for proactive measures to preserve these languages.